Disclosure and Self-Advocacy in Higher Education: Emerging into Adulthood with a Disability - Carol Rogers Shaw (Adult Education Research Conference, 2019)
A study of leaners with disabilities in postsecondary education moving from dependent special education K12 students to self-authored adult learners reveals complex disclosure and self-advocacy interactions with faculty, peers, and disability staff.
Keywords: disability; postsecondary education; emerging adulthood; self-authorship; disclosure; self-advocacy